2003
DOI: 10.1177/0011128703252679
|View full text |Cite
|
Sign up to set email alerts
|

Gang Membership and Acculturation: ARSMA-II and Choloization

Abstract: Choloization, a staple in gang research on Latinos, asserts that gang members are less acculturated than non-gang members. However, the concept has not been subjected to a quantitative analysis. Using a sample of Latino incarcerated youths from Los Angeles County (N = 370), the veracity of the concept of choloization using the ARSMA-II Acculturation Scale is examined. It was hypothesized that gang members have more of a Mexican orientation than non-gang members. The hypothesis was supported, providing empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…A fewer number of studies have examined acculturation relative to criminological variables including gang membership (Lopez and Brummett 2003;Miller et al 2009), domestic violence victimization (Hazen and Soriano 2007), and fear of crime (Brown and Benedict 2004). Collectively, these studies have indicated that higher levels of acculturation or assimilation are associated with a greater likelihood of negative outcomes.…”
mentioning
confidence: 99%
“…A fewer number of studies have examined acculturation relative to criminological variables including gang membership (Lopez and Brummett 2003;Miller et al 2009), domestic violence victimization (Hazen and Soriano 2007), and fear of crime (Brown and Benedict 2004). Collectively, these studies have indicated that higher levels of acculturation or assimilation are associated with a greater likelihood of negative outcomes.…”
mentioning
confidence: 99%
“…While various consequences exist for those who occupy marginalized social positions in institutional contexts, marginalized group members are particularly adept at identity negotiations (Boykin 1988;Lopez and Brimmett 2003;Mahalingam 2007a;Root 1999;Suarez-Orozco and Suarez-Orozco 2001). While discussing specific factors pertaining to ethnic minority children's identity development, Boykin (1988) indicated that minority children have faced a "triple quandary" where they are expected to negotiate cultural expectations of dominant culture, minority culture and their own ethnic culture.…”
Section: Social Marginalitymentioning
confidence: 99%
“…While discussing specific factors pertaining to ethnic minority children's identity development, Boykin (1988) indicated that minority children have faced a "triple quandary" where they are expected to negotiate cultural expectations of dominant culture, minority culture and their own ethnic culture. Lopez and Brimmett (2003) have studied whether social marginalization experienced in the form of alienation and disenfranchisement is a major contributing factor for the group cohesion of gang violence among Latino youth incarcerated in Los Angeles county. They found that gang members felt more marginalized and maintained a Mexican orientation than non-gang members.…”
Section: Social Marginalitymentioning
confidence: 99%
“…To understand this problem, we considered demographic factors and the functions and reasons for attraction to gangs. Poor adolescents~Ruble & Turner, 2000!, members of ethnic minorities~Belitz & Veldez, 1994Lopez, 2003;Portes & Rumbaut, 2001!, and increasing numbers of preadolescents~Bureau of Justice Assistance, 1997! have been attracted to and recruited by gangs.…”
Section: Gang Involvementmentioning
confidence: 99%